1997
DOI: 10.1071/s96048
|View full text |Cite
|
Sign up to set email alerts
|

Effects of animal effluents on the phosphorus sorption characteristics of soils

Abstract: Two groups of soils were examined to determine the effects of dairy, pig, or sewage effluent and other materials containing phosphorus (P) on their P sorption characteristics, using the Langmuir equation to estimate values of both sorption capacity and sorption strength. There were 19 soils (0-15 cm) from 6 sites in the Williams River catchment and 3 soils (0-100 cm) from Bermagui, all from coastal New South Wales. Effluent usually decreased P sorption capacities of the Williams River soils, and in 3 soils the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 6 publications
3
52
1
1
Order By: Relevance
“…The soils used in the present study had an organic matter content ranging from 6.7%, for the background soil, to between 5 and 10% for the highly variable wetland soils. Holford et al (1997) also found that effluent treated soils have the lowest P adsorption capacities, as well as decreased adsorption strength. Holford et al (1997), however, also stated that the blocking of P adsorption sites by organic anions in wastewaters may be partially offset by the creation of new sites on enlarged organic matter-Fe surface complexes, but these sites adsorb P very weakly and probably allow for subsequent desorption to occur.…”
Section: Phosphorus Adsorption Characteristicsmentioning
confidence: 95%
See 2 more Smart Citations
“…The soils used in the present study had an organic matter content ranging from 6.7%, for the background soil, to between 5 and 10% for the highly variable wetland soils. Holford et al (1997) also found that effluent treated soils have the lowest P adsorption capacities, as well as decreased adsorption strength. Holford et al (1997), however, also stated that the blocking of P adsorption sites by organic anions in wastewaters may be partially offset by the creation of new sites on enlarged organic matter-Fe surface complexes, but these sites adsorb P very weakly and probably allow for subsequent desorption to occur.…”
Section: Phosphorus Adsorption Characteristicsmentioning
confidence: 95%
“…P would have already saturated some of the wetland adsorption sites, thereby reducing the S max in the wetland soils. As well, organic anions, such as those found in wastewater, can form complexes with Fe and Al, thereby reducing the effectiveness for P retention in a soil (Holford et al 1997;Reddy et al 1998). Wetlands with predominately mineral soils are better P storage sinks than peatlands, which are characterized by a high organic content, and other organic soils (Reddy and Graetz 1981;Richardson 1985).…”
Section: Phosphorus Adsorption Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several processes are not represented by the laboratory sorption procedure and may result in such accumulation, for example, precipitation, evaporative concentration of P in solution at the soil's surface, slow sorption processes (as discussed by Barrow 1992 andHolford 1997), and effects on sorption capacity related to the addition of effluent constituents (e.g. formation of complexes between P, P-reactive cations, and effluent OC, as suggested by Holford et al 1997). Desorption studies were directed at finding information about the nature of P storage in these piggery effluent irrigated soils (Fig.…”
Section: Sorption and Desorptionmentioning
confidence: 99%
“…Unfortunately, the study described in Holford et al (1997) was unable to quantify P additions, other than those in the form of superphosphate, making comparisons between treatments difficult.…”
Section: Introductionmentioning
confidence: 99%